Preparatory information reduces gastroscopy-related stress in children as confirmed by salivary cortisol - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Background/Aims: This study aimed to determine whether the anxiety levels of pediatric patients who undergo endoscopy are reduced after receiving preparatory information about the endoscopic procedure by monitoring their salivary cortisol (s-cortisol) levels. Patients and Methods: A total of 184 children undergoing gastroscopy under sedoanalgesia were induded in the study. All the patients received a brief explanation of the endoscopic procedure. Patients were divided into two groups; Group Unexplained did not receive any further information other than a brief explanation of the procedure, Group Explained received more detailed explanation of the procedure. To determine anxiety levels, saliva specimens were taken on the day before the procedure to examine cortisol levels before and after endoscopy. Anxiety scores before endoscopy were calculated by the modified Yale Preoperative Anxiety Scale. Patients were monitored throughout sedoanalgesia, induding during the endoscopy, sedation and recovery, and total propofol dosages were recorded. Results: Eighty-nine children undergoing gastroscopy (age 11.55 +/- 252 years; 50.596 girls) constituted Group Explained and 95 children undergoing gastroscopy (age 11.44 +/- 2.66 years; 56.896 male) constituted Group Unexplained. The anxiety score, duration of sedation, endoscopy and recovery, propofol dose, pre- and post-endoscopy s-cortisol levels were significantly reduced in Group Explained. Conclusions: We demonstrated that when endoscopic procedure is explained broadly to a child, the procedural stress is significantly less, as measured by the s-cortisol levels and the anxiety questionnaire. It is important for the attending physician to explain all aspects of examination carefully.
Keywords: Endoscopy; preparatory information; procedural stress; salivary cortisol; GASTROINTESTINAL ENDOSCOPY; PSYCHOLOGICAL PREPARATION; SEDATION; ANXIETY; ANESTHESIA; BEHAVIOR; MUSIC